2014
DOI: 10.3389/fpls.2014.00663
|View full text |Cite
|
Sign up to set email alerts
|

Plant immunity in plant–aphid interactions

Abstract: Aphids are economically important pests that cause extensive feeding damage and transmit viruses. While some species have a broad host range and cause damage to a variety of crops, others are restricted to only closely related plant species. While probing and feeding aphids secrete saliva, containing effectors, into their hosts to manipulate host cell processes and promote infestation. Aphid effector discovery studies pointed out parallels between infection and infestation strategies of plant pathogens and aph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
134
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(137 citation statements)
references
References 95 publications
1
134
0
2
Order By: Relevance
“…Yet, it is clear that they both have the capacity to activate and suppress plant immune responses (55,66). Nematodes secrete effectors to suppress immune responses and increase virulence, and likely produce DAMPs.…”
Section: Additional Invaders: Viruses Nematodes and Insectsmentioning
confidence: 99%
“…Yet, it is clear that they both have the capacity to activate and suppress plant immune responses (55,66). Nematodes secrete effectors to suppress immune responses and increase virulence, and likely produce DAMPs.…”
Section: Additional Invaders: Viruses Nematodes and Insectsmentioning
confidence: 99%
“…In particular, this analysis highlighted the importance of wall-associated kinases and receptor-like kinases, particularly those containing the Domain of Unknown Function26 (Foyer et al, 2015). Similarities between plant-aphid and plant-pathogen interactions have been suggested by demonstration of the involvement of plant resistance factors such as the NB-LRR domain finality proteins and the BRASSINOSTERIOD INSENSITIVE1-ASSOCIATED RECEPTOR KINASE1 in plant responses to aphids (Bos et al, 2010b;Jaouannet et al, 2014;Prince et al, 2014). The perception of environmental threats results in the production of an oxidative burst that involves the generation of reactive oxygen species (ROS) in the apoplast (Bos et al, 2010a(Bos et al, , 2010bJaouannet et al, 2014).…”
mentioning
confidence: 90%
“…Similarities between plant-aphid and plant-pathogen interactions have been suggested by demonstration of the involvement of plant resistance factors such as the NB-LRR domain finality proteins and the BRASSINOSTERIOD INSENSITIVE1-ASSOCIATED RECEPTOR KINASE1 in plant responses to aphids (Bos et al, 2010b;Jaouannet et al, 2014;Prince et al, 2014). The perception of environmental threats results in the production of an oxidative burst that involves the generation of reactive oxygen species (ROS) in the apoplast (Bos et al, 2010a(Bos et al, , 2010bJaouannet et al, 2014). Increasing literature evidence suggests that aphid-induced increases in ROS levels, together with the differential expression of genes involved in ROS generation and responses to oxidative stress, are important in the plant response to aphids and to other phloem-feeding insects (Moloi and van der Westhuizen, 2006;Kerchev et al, 2012aKerchev et al, , 2012bMai et al, 2013Liang et al, 2015Borowiak-Sobkowiak et al, 2016).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The plant-aphid interaction is complex and highly dynamic, subject to continual change (Mello and Silva-Filho 2002). Recently, studies have shown that aphids secrete effectors that modulate plant defence responses (Bos et al 2010;Atamian et al 2013;Pitino and Hogenhout 2013) pointing to parallels between plant-pathogen and plant-insect interactions (Jaouannet et al 2014). It has been suggested that two different processes are involved in the elicitation of plant defence.…”
mentioning
confidence: 99%